Freeman-Sheldon Syndrome Associated with Hemophilia-A in a Newborn - Bilge Tanyeri Bayraktar; Süleyman Bayraktar; Hüseyin Arslan; Fatma Betül Çakır (Haseki Tıp Bülteni, 2016)
The Freeman-Sheldon syndrome (FSS) (whistling face) is a congenital autosomal dominant disease (rarely described in its autosomal recessive form) characterized by small “whistling” mouth, a flat mask-like face, joint contractures (commonly involving the fingers and hands) and underdevelopment of the nasal cartilage. Other clinical features include full forehead, deep set eyes, epicanthal folds, high palate, H-shaped cutaneous dimpling on the chin, ulnar deviation of the hands, seizures, and dislocation of the hip. A 10-day-old male newborn was admitted to our neonatal intensive care unit with jaundice and hyperthermia. He had fever of 42.5°C, small whistling mouth, a flat mask-like face, joint contractures of the fingers, and ulnar deviation of the hands. The parents were consanguineous and one of the boys died when he was 1 years old due to intracranial hemorrhage. To our knowledge, there have been more than 60 cases diagnosed with FSS. This is the first reported case of Freeman-Sheldon syndrome associated with hemophilia A and the second case of FSS associated with fever without anesthesia.